Dissection of transcriptional events in graft incompatible reactions of “Bearss” lemon (Citrus limon) and “Valencia” sweet orange (C. sinensis) on a novel citrandarin (C. reticulata × Poncirus trifoliata) rootstock - Febres, Vicente J.; Fadli, Anas; Meyering, Bo; Yu, Fahong; Bowman, Kim D.; Chaparro, Jose Xavier; Albrecht, Ute (Frontiers in Plant Science, 2024)
Citrus is commercially propagated via grafting, which ensures trees have consistent fruit traits combined with favorable traits from the rootstock such as soil adaptability, vigor, and resistance to soil pathogens. Graft incompatibility can occur when the scion and rootstock are not able to form a permanent, healthy union. Understanding and preventing graft incompatibility is of great importance in the breeding of new fruit cultivars and in the choice of scion and rootstock by growers. The rootstock US-1283, a citrandarin generated from a cross of 'Ninkat' mandarin (Citrus reticulata) and 'Gotha Road' #6 trifoliate orange (Poncirus trifoliata), was released after years of field evaluation because of its superior productivity and good fruit quality on 'Hamlin' sweet orange (C. sinensis) under Florida's growing conditions. Subsequently, it was observed trees of 'Bearss' lemon (C. limon) and 'Valencia' sweet orange (C. sinensis) grafted onto US-1283 exhibited unhealthy growth near the graft union. The incompatibility manifested as stem grooving and necrosis underneath the bark on the rootstock side of the graft. Another citrandarin rootstock, US-812 (C. reticulata 'Sunki' × P. trifoliata 'Benecke'), is fully graft compatible with the same scions. Transcriptome analysis was performed on the vascular tissues above and below the graft union of US-812 and US-1283 graft combinations with 'Bearss' and 'Valencia' to identify expression networks associated with incompatibility and help understand the processes and potential causes of incompatibility. Transcriptional reprogramming was stronger in the incompatible rootstock than in the grafted scions. Differentially expressed genes (DEGs) in US-1283, but not the scions, were associated with oxidative stress and plant defense, among others, similar to a pathogen-induced immune response localized to the rootstock; however, no pathogen infection was detected. Therefore, it is hypothesized this response could have been triggered by signaling miscommunications between rootstock and scion either through 1) unknown molecules from the scion that were perceived as danger signals by the rootstock, 2) missing signals from the scion or missing receptors in the rootstock necessary for the formation of a healthy graft union, 3) the overall perception of the scion by the rootstock as non-self, or 4) a combination of the above.